2004
DOI: 10.2165/00007256-200434150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Multiple Sclerosis

Abstract: The pathophysiology of multiple sclerosis (MS) is characterised by fatigue, motor weakness, spasticity, poor balance, heat sensitivity and mental depression. Also, MS symptoms may lead to physical inactivity associated with the development of secondary diseases. Persons with MS are thus challenged by their disability when attempting to pursue an active lifestyle compatible with health-related fitness. Although exercise prescription is gaining favour as a therapeutic strategy to minimise the loss of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
0
23

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(245 citation statements)
references
References 96 publications
6
210
0
23
Order By: Relevance
“…Further, exercise progression was well tolerated, as demonstrated by an increased workload for a longer duration with a lower overall rate of perceived exertion. Based on this finding, the least recommended dose of aerobic exercise 21 (frequency, twice per week; duration, two consecutive sessions of up to 15 minutes each; intensity, 50% to 70% of peak oxygen consumption per unit exercise may benefit individuals with MS. Furthermore, in our study, BDI-II Somato-Affective subscale scores remained improved after the 3-month period of unstructured physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, exercise progression was well tolerated, as demonstrated by an increased workload for a longer duration with a lower overall rate of perceived exertion. Based on this finding, the least recommended dose of aerobic exercise 21 (frequency, twice per week; duration, two consecutive sessions of up to 15 minutes each; intensity, 50% to 70% of peak oxygen consumption per unit exercise may benefit individuals with MS. Furthermore, in our study, BDI-II Somato-Affective subscale scores remained improved after the 3-month period of unstructured physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…To set the initial aerobic exercise intensity, we assessed cardiovascular function by continuously monitoring each participant's breath by breath gas analysis via a telemetry metabolic measurement system (MedGraphics VO 2000 ; MGC Diagnostics, St. Paul, MN) while performing the 6-Minute Walk (6MW) test according to American Thoracic Society guidelines. 8 Test order was standard- The initial target exercise training intensity on the UE/ LE ergometer and treadmill was set at 50% to 70% of oxygen consumption achieved 21 as established by the 6MW during session 1. We conducted aerobic testing to set an appropriate exercise goal and to monitor safety of the participants during exercise.…”
Section: Instrumentsmentioning
confidence: 99%
“…21,22 Some specific exercise guidelines for the MS population have been proposed. 1,12,23 In a comprehensive review of exercise and MS, White and Dressendorfer 1 suggested moderate aerobic exercise for a total of 20 to 30 minutes, alternating with rest periods, two to three times per week. Daily general flexibility exercises were also recommended.…”
Section: Activity Levels Of People With Ms and Exercise Recommendationsmentioning
confidence: 99%
“…In general, group 1 animals (demyelinated + exercise) had fewer errors when compared to group 2 (demyelinated + sedentary). In clinical studies, physical exercise practice by individuals with Ms has greatly benefited such patients [18][19][20] . one study showed that different types of exercise, including aquatic exercises, for Ms individuals with mild to moderate compromise lead to improved functional activities, execution of daily life activities, as well as decreased fatigue and improved quality of life of such individuals 20 .…”
Section: Fig 2 Scores Across Days In Groups 1 Andmentioning
confidence: 99%
“…In clinical studies, physical exercise practice by individuals with Ms has greatly benefited such patients [18][19][20] . one study showed that different types of exercise, including aquatic exercises, for Ms individuals with mild to moderate compromise lead to improved functional activities, execution of daily life activities, as well as decreased fatigue and improved quality of life of such individuals 20 . some aspects of the physical properties of water, such as buoyancy and viscosity, diminish the action of gravity and allow greater balance, movement amplitude, development of muscle strength and endurance, all contributing to improvement in symptomatology and functional deficits.…”
Section: Fig 2 Scores Across Days In Groups 1 Andmentioning
confidence: 99%